The Psychometric Properties of the Norwegian version of Child Behavior Checklist (CBCL) - Kornør, Hege; Jozefiak, Thomas (PsykTestBarn, 2012)
Description: CBCL is one of three instruments in the Achenbach System of Empirically Based Assessment (ASEBA). Thomas Achenbach and Leslie Rescorla have developed the instrument, published in English in their various original version in 1983, 1991 and 2001. Torunn S. Nøvik and Sonja Heyerdahl have translated the CBCL versions into Norwegian, published in 1986/88, 1993 and 2002. Caregivers of children aged 1 ½ to 18 years complete CBCL to assess competence and problem areas. There are two competence scales in CBCL 1 ½ - 5, and one Total scale divided into three subscales in CBCL 6-18. The Total Problems scale forms the basis for various subscales for syndromes or clusters of problem areas. Thus, CBCL facilitates a broad assessment of children’s emotional and behavioural problems. CBCL takes less than 30 minutes to complete. Requirements for users are test-related qualifications. The following professional qualifications are also required to administer and score CBCL: teacher, psychologist, physician or at least a bachelor’s degree or equivalent in health or social subjects. Literature search: Our systematic literature search identified 68 publications reporting CBCL data in Norwegian samples. Thirty eight of them reported psychometric data for CBCL 4-18 from 25 Norwegian studies. Two publications reported psychometric data for CBCL 6-18. We did not identify any psychometric evidence for the other CBCL versions. Psychometrics: One publication reported norms for CBCL 6-18 from a large sample of 6 to 16-year olds in the county of Sør-Trøndelag. We also found norms for CBCL 4-18 from samples in Oslo, Lofoten and Finnmark, among the included publications. The construct validity of CBCL 4-18 was studied by confirmatory factor analysis (N = 949; RMSEA = 0.039), and the criterion validity by sensitivity (40-83%) and sensitivity (70-94%) (N= 56-83) calculations. Internal consistency was measured by Cronbach’s alpha (≥ 0.8) for the problem scales, but more variable for the subscales. We found no measures of other types of reliability. Conclusion: Despite a great number of publications about CBCL, evidence for the psychometric properties of the versions for the youngest age group is absent, and there were only two publications about the most recent CBCL version for the oldest age group. The basis for CBCL national norms is limited due to local populations with low to moderate response rates and very variable sample sizes. The construct validity can be characterized as good, and the criterion validity as promising. The internal consistency of the problem scales was good to excellent. Even though the total evidence seems promising, the instrument should be used with some caution, and more research is desirable, especially in the youngest age group.